Competition For Jurisdiction Over Food Industry in South Korea - SUNGEUN PARK (Jurnal Studi Pemerintahan, 2011)
In spite of the government’s multilateral effort to control food safety, there have been constantly manyshock events threatening citizens’ health. This paper points out the matter of food safety managementsystem with a view of competition for jurisdiction over food industry among the Ministry of Healthand Welfare and the Ministry for Food, Agriculture, Forestry and Fisheries and affiliatedorganizations. Use description qualitative method in research. Each ministry has separate basicpositions and approaches to food industry policy: regulation and promotion.The policy image has beenchanged into “regulation” as public anxiety and concern for hazardous foods has grown since the endof 1990. They competeto take charge of promoting or regulating the food industry by establishing oramending laws, expanding organizations and mobilizing a coalition.Coordination by policy committee,cooperation between agencies, and integration of agencies were introduced as measures to eliminateunnecessary competition for jurisdiction.